Comparative Analysis of Data Mining Techniques to Predict Heart Disease for Diabetic Patients - Kumar A.; Kumar P.; Srivastava A.; Ambeth Kumar V.D.; Vengatesan K.; Singhal A. (My University, 2025)
The healthcare sectors have many difficulties and challenges in finding diseases. Healthcare organizations are collecting bulk amount of patient data. The Data mining methods are utilized to decide covered data that is valuable to healthcare specialists with effective analytic decision making. Data mining strategies are utilized in the field of the healthcare industry for different purposes. The objective of this paper is to assess and analyze using three unique data mining arrangement methods, for example, Naïve Bayes (NB), Support Vector Machine (SVM) and Decision Tree to decide the potential approaches to predict the possibility of heart disease for diabetic patients dependent on their predictive accuracy. © 2020, Springer Nature Singapore Pte Ltd.